Implementasi Reduksi Keadaan Rangkaian Digital Sekuensial Metode Bagan Implikasi - Ari Setiyani, Theresia Prima; Suyanto, Yohanes (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2019)
The implementation of state reduction in sequential digital circuits is made for learning the topic of state reduction. The method used for state reduction is an implication chart. This method starts with reading the transition table state and transfered into the array structure. Based on this array structure a table or chart of initial implications is arranged. The next process is to change the contents of the table if there are cells that meet the requirements to be declared as identical or not identical. This process is repeated continuously until there is no change in cell contents. The state of reduction implementation is made using the Python programming language and PHP. The results of the implementation are successful for the state transition table with 1 input and 1 output.